Smetanabatrus kinabalu (Staphylinidae: Pselaphinae: Batrisitae), a new genus and new species from Sabah, Borneo - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2013)
A new genus and new species of the pselaphine tribe Batrisini, Smetanabatrus kinabalu gen. et sp. n., is described from Sabah, East Malaysia. Both sexes of the new species have securiform maxillary palpi, with the male exhibiting extreme abdominal modification. Illustrations of the habitus and major diagnostic features, as well as a discussion on the taxonomic placement of the new taxon is provided. A key to genera of the Batrisini from Borneo is provided.